2011
DOI: 10.1021/jm200911r
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent and Highly Selective Thienopyridine Janus Kinase 2 Inhibitors

Abstract: Developing Janus kinase 2 (Jak2) inhibitors has become a significant focus for small molecule drug discovery programs in recent years due to the identification of a Jak2 gain-of-function mutation in the majority of patients with myeloproliferative disorders (MPD). Here, we describe the discovery of a thienopyridine series of Jak2 inhibitors that culminates with compounds showing 100- to >500-fold selectivity over the related Jak family kinases in enzyme assays. Selectivity for Jak2 was also observed in TEL-Jak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Consequently, neither a K i nor an IC 50 measurement at ATP Km in an enzymatic assay represents a good evaluation of cellular activity for ATP competitive inhibitors. 23,24,25 Consequently, to assess the profile of compound 65 in potentially more relevant cellular settings, its potency and selectivity was determined in cellular and whole blood assays. In recent years the importance of the JAKs in the heterodimeric pair has been the source of intensive research.…”
Section: Good Aqueous Solubility and Ppb With Improved Potencymentioning
confidence: 99%
“…Consequently, neither a K i nor an IC 50 measurement at ATP Km in an enzymatic assay represents a good evaluation of cellular activity for ATP competitive inhibitors. 23,24,25 Consequently, to assess the profile of compound 65 in potentially more relevant cellular settings, its potency and selectivity was determined in cellular and whole blood assays. In recent years the importance of the JAKs in the heterodimeric pair has been the source of intensive research.…”
Section: Good Aqueous Solubility and Ppb With Improved Potencymentioning
confidence: 99%
“…JAK3 inhibition has immunosuppressive effects. Amgen (Thousand Oaks, CA) reported a series of thienopyridine compounds as selective and potent JAK2 inhibitors [31]. Compound 14 was the most potent JAK2 inhibitor with the highest selectivity over the other JAK family kinases.…”
Section: Key Termmentioning
confidence: 99%
“…The key to achieving selectivity appears to be the nature of the aryl or heteroaryl group attached to the pyrrolidine nitrogen in structures of the form (19). That this can result in highly selective agents is illustrated by the compounds (20) and (21), the most selective shown of each of the two subsets of compounds, respectively, 132.5-and 53.3-fold selective for JAK1 relative to JAK2. However, the nicotinonitrile derivative (22) is the clearly preferred compound (Figure 4).…”
Section: Incytementioning
confidence: 99%
“…This has led to diverse chemotypes being identified as providing selectivity for these kinases. JAK2 selective inhibitors have been identified by Rigel (R-723) [15], Ambit (AC-430) [16,17], Cephalon (CEP-33779) [18], Bristol-Myers Squibb (BMS-911543) [19] and Amgen (1) [20] (Figure 1), whereas JAK3 selective inhibitors have been identified by Novartis (2) [21], Roche (3) [22] and Vertex (VX-509) ( Figure 2). VX-509 has progressed to Phase II studies in rheumatoid arthritis and has been reported to show < 10-fold selectivity for JAK3 at the kinase level but considerably better selectivity in cellular assays [23].…”
Section: Introductionmentioning
confidence: 99%